Fuir les métropoles : les habitats alternatifs en milieu rural comme espaces de refuge et de contestation - Madeg Leblay (Métropoles, 2021)
In this paper we investigate a specific type of protest against metropolises: cohousing and everyday practices in rural spaces, away from urban centers. We refer to an ethnographic study on several rural eco-cohousing places in order to show that they can exist both as refuges and contentious spaces for individuals who are discontent with their life in existing metropolises. We cannot immediately assign critical and political intentions to the inhabitants that we have met. Actually, they do not explicitly protest against metropolises or metropolisation, contrary to some contemporary urban social movements. However, their biographical trajectories as well as their everyday practices indicate a choice that go beyond a simple residential move. We explain that this peculiar style of protest corresponds to what has already been theorised as prefigurative politics. It implies both a depoliticisation of usual contentious politics and a politicisation of domestic spaces.